First prospective, single-arm, multicenter study to evaluate safety and efficacy of the overall thrombectomy system -iNedit, iNdeep, and iNtercept- for acute ischemic stroke. Rationale beyond the study - San Román, Luís; Gramegna, Laura Ludovica; Pich, Sara; Domingo-Rodriguez, Laura; Duran, Marta; Duocastella, Lluís; Macho, Juan (Frontiers in Neurology, 2025)
RationaleThe clinical impact of a novel mechanical thrombectomy strategy, which integrates distal access with flow reversal and flow arrest via a distal balloon, all within a single procedure [Safety and Efficacy of the overall throMbectomy system for sTroke (SEMTiC) strategy], has not been tested.AimThe SEMTiC-01 study is the first prospective, multicenter in vivo study evaluating the safety and efficacy of the combined thrombectomy system—iNedit, iNdeep, and iNtercept—in patients with acute ischemic stroke.Sample size estimatesThe study was designed with a sequential structure based on the efficacy endpoint (eTICI ≥2b) reported in the literature [71.1% with a 95% confidence interval of (68.5%, 73.8%)]. An interim analysis was set for 115 patients and a final analysis for 225 patients, ensuring 98% power at a one-sided 0.025 significance level, with a 2.6% non-inferiority margin and a 15% assumed withdrawal rate.DesignSEMTiC-01 is a prospective, multicenter, single-arm, open-label clinical safety and efficacy investigation.OutcomePrimary efficacy endpoint: expanded treatment in cerebral infarction score (eTICI) ≥2b revascularization within ≤ 3 stent retriever passes. Primary safety endpoint: monitoring serious adverse events within 24 h post-intervention and all-cause mortality at 90 days.